2009
DOI: 10.1111/j.1745-6924.2009.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Racism on Ethnic Minority Mental Health

Abstract: A problem in ethnic minority mental health that can be solved in the foreseeable future is understanding how subtle and covert forms of racism affect psychological health of racial minorities. Although scientific psychology has generated a large body of literature on racial prejudice, stereotypes, intergroup attitudes, and racial bias and their often implicit and automatic nature, relatively little is known about the effects of these subtle racial bias on minority individuals. Following a selective review of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 27 publications
0
56
0
Order By: Relevance
“…Based on the literature we reviewed, the negative impact of racial microaggressions on psychological and physical health is beginning to be documented; however, these studies have been largely correlational and based on recall and self-report, making it difficult to determine whether racial microaggressions actually cause negative health outcomes and, if so, through what mechanisms (Okazaki 2009). Research focusing on the immediate psychological, physiological, and behavioral reactions to experiences of racial microaggressions may improve our understanding of the mechanisms through which racial microaggressions influence mental and physical health, and examining the entire process model will help shed light on how subtle forms of discrimination actually affect the daily well-being of racial and ethnic minorities.…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the literature we reviewed, the negative impact of racial microaggressions on psychological and physical health is beginning to be documented; however, these studies have been largely correlational and based on recall and self-report, making it difficult to determine whether racial microaggressions actually cause negative health outcomes and, if so, through what mechanisms (Okazaki 2009). Research focusing on the immediate psychological, physiological, and behavioral reactions to experiences of racial microaggressions may improve our understanding of the mechanisms through which racial microaggressions influence mental and physical health, and examining the entire process model will help shed light on how subtle forms of discrimination actually affect the daily well-being of racial and ethnic minorities.…”
Section: A Review and Critique Of Racial Microaggressions Literaturementioning
confidence: 99%
“…Given the rapid growth, yet relative infancy, as a theoretical and research topic, conceptual and methodological issues remain to be addressed in the following three domains: (1) what is the concept of racial microaggressions (e.g., Harris 2008); (2) why do racial microaggressions matter (i.e., how do racial microaggressions impact mental health and health; e.g., Okazaki 2009); and (3) how can racial microaggressions be best studied (e.g., Lau and Williams 2010). To this end, the purpose of this paper is to provide a review of racial microaggressions research literature in psychology since 2007 in order to elucidate how a clear taxonomy (Sue et al 2007a, b) has influenced research in psychology, how that research furthers our understanding of racial microaggressions as a psychological phenomenon, and what critical conceptual and methodological issues still remain.…”
mentioning
confidence: 99%
“…According to the subordinate male target hypothesis, minority men are subject to more experiences of discrimination than minority women. 43 According to subordinate male hypothesis, we expect more discrimination against males across various ethnic minority groups. Based on this theory it is not race but the intersection of race and gender that determines social pattering of discrimination.…”
Section: Assarimentioning
confidence: 99%
“…41 Most of the research on race by gender differences in bias is focused on explicit, rather than implicit bias. 42 While explicit bias results in mental and behavioral health problems, 23,24,43 there is a need to study factors that shape social patterning of implicit bias as well, which influences a wide range of domains such as interaction and quality of health care. [29][30][31][32] The current study was conducted to test race by gender differences in implicit bias against Blacks.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of these seemingly petty encounters can be a chronic stressor that erodes Asian Americans' coping resources and abilities, subsequently affecting their overall well-being. Indeed, available research findings have indicated the adverse effects of racism influence every aspect of Asian Americans' lives, including their physical and mental health outcomes and rates of substance abuse (Ahmed, Mohammed, & Williams, 2007;Brondolo, Gallo, & Myers, 2009;Chae, Takeuchi, Barbeau, Bennett, Lindsey, Stoddard, et al, 2008;Evans-Campbell, Lincoln, & Takeuchi, 2007;Gee et al, 2009;Kim et al, 2012;Liang et al, 2010;Okazaki, 2009;Spencer, Chen, Gee, Fabian, & Takeuchi, 2010;Yip et al, 2008). However, a plausible alternative explanation is that experiencing more RDEs leads to greater critical ethnic awareness of the social injustices regularly endured by Asian Americans.…”
Section: Discussionmentioning
confidence: 97%